Appropriateness of initial dose of non-vitamin K antagonist oral anticoagulants in patients with non-valvular atrial fibrillation in the UK. Issue 9 (20th September 2019) - García Rodríguez, Luis Alberto; Martín-Pérez, Mar; Vora, Pareen; Roberts, Luke; Balabanova, Yanina; Brobert, Gunnar; Fatoba, Samuel; Suzart-Woischnik, Kiliana; Schaefer, Bernhard; Ruigomez, Ana
Abstract : Objective: To evaluate the appropriateness of the initial prescribed daily dose of non-vitamin K antagonist oral anticoagulants (NOACs) according to label in patients with non-valvular atrial fibrillation (NVAF) in the UK. Design: Population-based cross-sectional study. Setting: UK primary care. Population: 30 467 patients with NVAF and a first prescription for apixaban, dabigatran or rivaroxaban between January 2011 and December 2016. Main outcome measures: Percentage of patients prescribed a NOAC dose according to the European Union (EU) labels (appropriately dosed), and not according to the EU labels (inappropriately dosed—including both underdosed and overdosed patients); percentage of patients prescribed an initial NOAC dose according to renal function status. Results: A total of 15 252 (50.1%) patients started NOAC therapy on rivaroxaban, 10 834 (35.6%) on apixaban and 4381 (14.4%) on dabigatran. Among patients starting NOAC therapy on rivaroxaban, 17.3% were eligible to receive a reduced dose compared with 12.8% of patients starting on apixaban and 53.8% of patients starting on dabigatran. The majority of patients were prescribed an appropriate dose according to the EU labels: apixaban 74.9 %, dabigatran, 74.4%; rivaroxaban, 84.2%. Underdosing occurred in 21.6% (apixaban), 8.7% (dabigatran), 9.1% (rivaroxaban). Overdosing was more frequent for dabigatran (16.9%) than for rivaroxaban (6.6%) or apixaban (3.5%). There was a trend towards dose reduction with increasing renal impairment. Among patients with severe renal impairment, the majority received a reduced dose NOAC: apixaban, 91.1%, dabigatran, 80.0%, rivaroxaban, 83.0%. Conclusion: Between 2011 and 2016, the majority of patients starting NOAC therapy in UK primary care were prescribed a daily dose in line with the approved EU drug label. Underdosing was more than twice as common among patients starting on apixaban than those starting on dabigatran or rivaroxaban. Research into the patient characteristics that may influence inappropriate underdosing of NOACs in UK primary care is warranted.